Pengaruh Koordinasi terhadap Efektivitas Program Pembangunan di Desa Pattirolokka Kecamatan Keera Kabupaten Wajo - Yuniarni Yusuf; Ardiyanti Burhan; Risma Risma (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
This study aims to reveal the impact of coordination on program effectiveness, focusing on Pattirolokka Village, Keera District, Wajo Regency. Effective coordination among relevant parties at the village level is a key factor in determining the success of rural development program implementation. To achieve this goal, data was collected through direct observation, the distribution of questionnaires, and gathering supporting data in the form of official documents. The results show that coordination has a positive and significant impact on program effectiveness in Pattirolokka Village. Good coordination between the village government, the community, and related institutions facilitates the implementation process and achieves the desired outcomes. Overall, the study indicates that coordination in this village is categorized as fairly good, which contributes to the effectiveness of the program, also categorized as fairly good. The success of this coordination is marked by an increase in community participation in various development activities and more optimal management of village resources. However, some aspects of coordination still need improvement, such as communication between the village government and the community, as well as evaluation of program implementation. Therefore, strengthening coordination between the village government and the community is crucial to improving the effectiveness of rural development programs, which will ultimately contribute to enhancing the welfare of the community in Wajo Regency. This study recommends that the relevant parties continue to improve coordination and communication mechanisms to achieve better results in the implementation of village development programs.